Paul Maenz Köln Jahresbericht 1974 : Askevold - Barry - Boyrle - Feldmann - Haacke - Paolini - Roehr - Rückriem - Salvo - Wery. - Paul Maenz, Köln; Paul Maenz, Brussel (Köln : Paul Maenz, 1974)
Askevold, David ; Barry, Robert ; Boyle, Mark ; Feldmann, Hans-Peter ; Haacke, Hans ; Paolini, Giulio ; Roehr, Peter ; Rückriem, Ulrich ; Salvo ; Wéry, Marthe
Duits
boek